Cost‐effective treatment of low‐risk carcinoma not invading bladder muscle. (7th September 2012) - Green, David A.; Rink, Michael; Cha, Eugene K.; Xylinas, Evanguelos; Chughtai, Bilal; Scherr, Douglas S.; Shariat, Shahrokh F.; Lee, Richard K.
Abstract : Study Type – Therapy (cost effectiveness analysis) Level of Evidence 2a What's known on the subject? and What does the study add? Bladder cancer is one of the costliest malignancies to treat throughout the life of a patient. The most cost‐effective management for low–risk non‐muscle‐invasive bladder cancer is not known. The current study shows that employing cystoscopic office fulguration for low‐risk appearing bladder cancer recurrences can materially impact the cost‐effectiveness of therapy. In a follow‐up protocol where office fulguration is routinely employed for low‐risk bladder cancers, peri‐operative intravesical chemotherapy may not provide any additional cost‐effectiveness benefit. OBJECTIVE: To examine the cost‐effectiveness of fulguration vs transurethral resection of bladder tumour (TURBT) with and without perioperative intravesical chemotherapy (PIC) for managing low‐risk carcinoma not invading bladder muscle (NMIBC). Low‐risk NMIBC carries a low progression rate, lending support to the use of office‐based fulguration for small recurrences rather than traditional TURBT. MATERIALS AND METHODS: A Markov state transition model was created to simulate treatment of NMIBC with vs without PIC, with recurrence treated by formal TURBT vs treatment with fulguration. Costing data were obtained from the Medicare Resource Based Relative Value Scale. Data regarding the success of PIC were obtained from the peer‐reviewed literature, as were corresponding utilities for bladder cancer‐related procedures. Sensitivity analyses were performed. RESULTS: At 5‐year follow‐up, a strategy of fulguration without PIC was the most cost‐effective (mean cost‐effectiveness = US 654.8/quality‐adjusted life year), despite a lower recurrence rate with PIC. Both fulguration strategies dominated each TURBT strategy. Sensitivity analysis showed that fulguration without PIC dominated all other strategies when the recurrence rate after PIC was increased to ≥14.2% per year. Similarly, the cost‐effectiveness of TURBT becomes more competitive with fulguration when the total cost of TURBT declines < US 1175. CONCLUSIONS: The present study shows that fulguration without PIC was the most cost‐effective strategy for treating low‐risk NMIBC. The effectiveness of PIC and the cost of TURBT can materially impact the cost‐effectiveness of the different management strategies. These results should be considered in treatment decisions in the context of preserving oncological control.